Pengaruh Leverage, Profitabilitas Dan Capital Intensity Ratio Terhadap Effective Tax Rate - Mawardi, Ilham; Ratnawati, Vince; Mela, Nanda Fito (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2022)
Penelitian guna melihat pengaruh leverage, profitabilitas dan capital intensity ratio bagi effective tax rate. Populasi yakniperusahaan industry terdaftar di Bursa Efek Indonesia 2016- 2019. Memakai teknik purposive sampling sebanyak 312.Pengambilan data dokumentasi laporan keuangan serta tahunan. Analisis data yan dipakai ialah uji asumsi klasik, analisisdeskriptif dan analisis regresi linier berganda. Menyebutkan leverage, peluang/kemungkinan dan capital intensity ratioberdampak bagi effective tax rate. This Research is aimed to analyze effect of leverage, profitability and capital intensity ratio related effective tax rate. The population in this study were manufacture companies listed on the Indonesia Stock Exchange from 2016 to 2019. The sampling technique used the purposive sampling technique and obtained a sample of 312 samples. Analysis of the data used is a documentation technique from company’s financial report and company’s annual report. The method of data analysis used classical assumption test, descriptive analysis, and multiple regression analysis. The results of this study indicate that leverage, profitability and capital intensity ratio have a significant effect related to effective tax rate.